Research on the Influence of Supply Chain Digitalization on Enterprise Value - Tian, Ran; Yang, Hanting; Han, Xinlin; Li, Zihe (Transactions on Economics, Business and Management Research, 2024)
With the help of the exogenous impact environment constructed by the pilot project of supply chain innovation and application, based on the data of listed companies in Shanghai and Shenzhen A-shares from 2008 to 2019, this paper systematically investigates the impact of supply chain digitalization on enterprise value. It is found that the digitalization of the supply chain has significantly improved the enterprise value. The intermediary effect test shows that the digitalization of the supply chain can enhance enterprise value by improving the internal control level of enterprises. The results of heterogeneity analysis show that the digitalization of the supply chain plays a more significant role in enhancing the value of non-high-tech enterprises and non-state-owned enterprises. In further research, it is found that government support and supply chain digitalization complement each other to enhance enterprise value. The conclusions provide important policy implications for promoting the effective transformation and efficiency improvement of supply chain digitalization of market enterprises.